HBR guide to managing stress at work. - Yen, Jonathan (Harvard business review guides., 2022)
Are you suffering from work-related stress? Feeling overwhelmed, exhausted, and short-tempered at work-and at home? Then you may have too much stress in your life. Stress is a serious problem that impacts not only your mental and physical health, but also your loved ones and your organization. So what can you do to address it? The HBR Guide to Managing Stress at Work will help you find a sustainable solution. It will help you reach the goal of getting on an even keel-and staying there. You'll learn how to: harness stress so it spurs, not hinders, productivity; create realistic and manageable routines; aim for progress, not perfection; make the case for a flexible schedule; ease the physical tension of spending too much time at your computer; and renew yourself physically, mentally, and emotionally.